Hiattville, Bourbon County - Vincent, Katelyn (Kansas State University, The Chapman Center for Rural Studies, 2012)
Hiattville was once a booming town, its population increasing from 50 to 500 in the 1880s. Many residents left after a 1905 fire, and the post office finally closed in 1986.
Katelyn Vincent, “Hiattville, Bourbon County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/139.
Keywords: Bourbon County; Hiattville; Pawnee Indians; Railroad; Kansas; Fire